Acceptability and factors associated with the community nutrition service for children under two years of age by mothers in the Degadamot district, west Gojjam, Ethiopia, 2023 - Teshome Demis Nimani; Feyisa Shasho Bayisa; Sara Debebe Jimma; Ashenafi Abebe Latebo (Clinical Epidemiology and Global Health)
Background: Malnutrition accounts for 45 percent of children under five years of age in Ethiopia and is a more common problem in rural communities. In this regard, Ethiopia has implemented the Community Based Neutrition (CBN) program at the community level to improve the nutritional status of children. Despite this, malnutrition still causes a significant rate of child morbidity and mortality. The status of the implementation of the CBN program is unknown. Methods: A single case study design was employed from March 28 to April 28, 2023. A total of 407 systematically selected mothers for exit interviews participated in the study. The data was entered into Epi-Inf version 7 and exported to STATA version 17 for analysis. Multivariate logistic regression was performed to determine the factors associated with the acceptability of mothers. Findings were presented using descriptions, tables, and graphs. Results: According to the predetermined judgment parameter, the acceptability of CBN services by mothers (66.6 %). Rural residence 0.28 (AOR = 0.28, 95 % CI 0.106, 0.754), merchant 0.11 (AOR = 0.11, 95 % CI 0.036, 0.47), primary 2.5 (AOR = 2.53, 95 % CI 1.09, 5.85), secondary 3.29 (AOR = 3.29, 95 % CI 1.03, 8.43), and higher education 1.46 (AOR = 1.46, 95 % CI 1.09, 4.05) were significantly associated with acceptability. Conclusions: The general acceptability of the mother to community nutrition services was measured fairly according to the predetermined judgment parameter. Educating mothers is an important factor in increasing service acceptability.